Indications for Caesarean Section and its Fetal and Maternal Outcome in a Teaching Hospital, Province Five, Nepal - Panth, Asha; Bhattarai, Saraswoti Kumari Gautam; Acharya, Sunita (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Cesarean section (CS) is an operative technique by which a fetus is delivered through an abdominal and uterine incision and is effective in saving maternal and infant lives but caesarean section rates higher than 10% are not associated with reductions in maternal and newborn mortality rates. The objective of the study was to find out the indications for caesarean section and its fetal and maternal outcomes in a Teaching Hospital, Province Five, Nepal. Methods: A descriptive, cross-sectional study was conducted in a teaching hospital, Nepal. A total of 150 purposively selected postnatal mothers after caesarean section were interviewed by face to face technique using a structured interview schedule. Analysis and interpretation of the findings were done with the help of descriptive and inferential statistics. Results: The study shows that the majority (93.3%) of mothers had undergone an emergency caesarean section and the majority (92%) had maternal indications for caesarean section. Among them, one third had a previous caesarean section followed by 14.5% obstructed labor. Fetal indications include breach (44.4%), fetal distress (29.6%), big baby (11.1) and twins and triplets (3.7%). Only (10.7%) had an unfavorable fetal outcome which includes the need for Neonatal Intensive Care Unit (NICU) (31.2%) followed by neonatal death (25%). Only three mothers (2%) had an unfavorable maternal outcome which includes Post-Partum Hemorrhage (PPH); need for blood transfusion and fever respectively. There is no statistically significant association between sociodemographic characteristics and type of caesarean section. There is a statistically significant association between the previous history of caesarean section and type of caesarean section (P= .005). Conclusions: Previous caesarean section was the most common indication for caesarean section. Unfavorable outcome after caesarean section was considerably present which needs to be addressed.